Effect of a Nurse-Led Multimodal Intervention on Glycaemic Control among Primary Care Patients with Type 2 Diabetes: A Quasi-Experimental Study - Azwaldi; Ismar Agustin; Imelda Erman (Postgraduate, University of Mataram, 2026)
Aims: This study sought to determine the impact of a nurse-led multimodal intervention on glycaemic control in patients with type 2 diabetes receiving care in a primary care setting. Methods: A quasi-experimental study was conducted involving 36 patients with type 2 diabetes attending primary care services, with 19 participants assigned to the intervention group and 17 to the control group. Patients in the intervention group received care from nurses using a structured multimodal intervention programme, while those in the control group continued with usual care. Glycaemic control was assessed using glycated haemoglobin (HbA1c) levels and glycaemic risk stratification before and after the intervention. Results: At four weeks, the intervention group demonstrated a mean reduction in HbA1c of 0.37%, whereas the control group showed a mean increase of 0.11%. In addition, 63% of participants in the intervention group showed improvement in glycaemic risk category, compared with 78% of control group participants who remained in the highest risk category. The greatest improvement was observed among patients with baseline HbA1c levels ≥8.0%. However, statistical significance values (e.g., p-values and effect sizes) were not reported in this study. Conclusions: In primary care settings, a nurse-led multimodal intervention was associated with improved glycaemic control among patients with type 2 diabetes. These findings suggest that structured nursing interventions may contribute to better diabetes management and risk stratification, particularly in patients with poor baseline glycaemic control.